God's Messiah in the Old Testament: expectations of a coming king - Abernethy, Andrew T. (Baker Academic, a division of Baker Publishing Group, 2020)
"Two respected Old Testament scholars offer a fresh, comprehensive treatment of the Messiah theme throughout the entire Old Testament and examine its relevance for New Testament interpretation"--